Cultural evolution and environmental change in Central Europe between 40 and 15 ka. (20th April 2021) - Maier, A.; Stojakowits, P.; Mayr, C.; Pfeifer, S.; Preusser, F.; Zolitschka, B.; Anghelinu, M.; Bobak, D.; Duprat-Oualid, F.; Einwögerer, T.; Hambach, U.; Händel, M.; et al.
Abstract: The role of environmental change in the evolution of cultural traits is a topic of long-standing scientific debate with strongly contrasting views. Major obstacles for assessing environmental impacts on the evolution of material culture are the fragmentary nature of archaeological and – to a somewhat lesser extent – geoscientific archives and the insufficient chronological resolution of these archives and related proxy data. Together these aspects are causing difficulties in data synchronization. By no means does this paper attempt to solve these issues, but rather aims at shifting the focus from demonstrating strict chains of causes and events to describing roughly contemporaneous developments by compiling and comparing existing evidence from archaeology and geosciences for the period between 40 and 15 ka in Central Europe. Analysis of the archaeological record identifies five instances at around 33, 29, 23.5, 19, and 16 ka, for which evidence suggests an increased speed of cultural evolution. By comparing data from different geoscientific archives, we discuss whether or not these instances have common characteristics. We stress that common characteristics per se are no proof of causality; repeated co-occurrences of certain features over long periods of time, however, suggest that certain explanations may be more plausible than others. While all five cases roughly coincide with pronounced and rapid environmental changes, it is also observed that such conditions do not necessarily trigger major changes in the material culture. Increases and decreases in the diversity of cultural traits seem to be rather correlated with the overall demographic development. In compiling and comparing our data, we also identify periods with high need and potential for future research regarding the relation between environmental change and cultural evolution.